2020
DOI: 10.1101/2020.02.27.967372
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rtrack: a software package for reproducible automated water maze analysis

Abstract: Rtrack is an open-source software package for the analysis of spatial exploration data from behavioural tests such as the Morris water maze. The software provides an easy-touse interface for data import, analysis and visualisation. A parameter-free machine learning model allows rapid and reproducible classification of spatial search strategies. We also propose a standard export format to enable cross-platform data sharing for the first time in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Search strategy use was analyzed using a machine learning classifier package in R called RTrack [ 116 ] (Fig. 2 d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Search strategy use was analyzed using a machine learning classifier package in R called RTrack [ 116 ] (Fig. 2 d).…”
Section: Resultsmentioning
confidence: 99%
“…Raw data from Ethovision (Noldus) was obtained and analyzed using the Rtrack in R, a package for reproducible and automated water maze analysis using a machine learning classifying strategy [ 116 ]. Metrics obtained from this package were latency to platform, time in goal zone, and search strategy classification.…”
Section: Methodsmentioning
confidence: 99%
“…Our group recently showed that, in aged mice, assessment of navigational learning strategies revealed important aspects of cognition that would not necessarily be apparent when assessing behavioral performance alone (Berdugo-Vega et al, 2020). Hence, we tested GFP and 4D-injected mice 4 weeks after tamoxifen administration to evaluate their evolution in the use of hippocampus-dependent and spatially-precise strategies over time by using an automated machine learning model that assesses swimming trajectories (Overall et al, 2020).…”
Section: Increased Neurogenesis Promotes Spatial Navigation and Fleximentioning
confidence: 99%
“…Finally, we analysed a publicly available dataset with two strains of mice (10-week old female mice C57Bl/6J and DBA/2J) tested in a goal reversal task (Overall et al, 2020). These analyses highlight the power of the current vector field property-based measures in detecting search centers.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, such methods can detect multiple search strategies within a given MWM session (Cooke et al, 2019; Vouros et al, 2018). A parameter free machine learning based algorithm was also developed to classify MWM search strategies (Overall et al, 2020). This approach is automated and uses trajectories to assign performances in individual trials to different classes.…”
Section: Introductionmentioning
confidence: 99%